Peran Sistem Customer Relationship Management dalam Meningkatkan Mutu Layanan Kesehatan - Huwae, Lourenz Simon; Sillehu, Sahrir; Nafiah, Nilam Cahya; Kristoforus, Josefus (FORIKES, 2025)
Innovative strategies are needed to improve the quality of patient care, one of which is customer relationship management, a system focused on sustainably managing patient relationships through the integration of technology, processes, and human resources. The purpose of this study is to comprehensively review the role of customer relationship management in improving the quality of healthcare services, including patient satisfaction, operational effectiveness, and managerial aspects. The method used in this study is a literature review of various relevant recent studies, including national and international publications from the past eight years. The results indicate that the implementation of customer relationship management in the healthcare sector can improve communication between healthcare professionals and patients, accelerate the service process, and support data-driven decision-making. Furthermore, customer relationship management also plays a crucial role in building patient loyalty through personalized services and continuous monitoring of individual health needs. However, the implementation of customer relationship management still faces several challenges, including limited technological infrastructure, workforce resistance, and issues of patient data privacy and security. In conclusion, customer relationship management is a strategic instrument that contributes significantly to improving the quality of healthcare services, as long as its implementation is supported by policies, regulations, and organizational resource readiness.Keywords: customer relationship management; healthcare quality; patient satisfaction; information technology ABSTRAK Strategi inovatif diperlukan untuk meningkatkan mutu pelayanan kepada pasien, yang salah satunya adalah customer relationship management, yaitu sistem yang berfokus pada pengelolaan hubungan dengan pasien secara berkelanjutan melalui integrasi teknologi, proses, dan sumber daya manusia. Tujuan studi ini adalah meninjau secara komprehensif peran customer relationship management dalam meningkatkan mutu layanan kesehatan, baik dari aspek kepuasan pasien, efektivitas operasional, maupun manajerial. Metode yang digunakan dalam studi ini adalah tinjauan literatur terhadap berbagai penelitian terkini yang relevan, mencakup publikasi nasional maupun internasional dalam kurun 8 tahun terakhir. Hasil kajian menunjukkan bahwa penerapan customer relationship management dalam sektor kesehatan mampu meningkatkan komunikasi antara tenaga kesehatan dan pasien, mempercepat proses pelayanan, serta mendukung pengambilan keputusan berbasis data. Selain itu, customer relationship management juga berperan penting dalam membangun loyalitas pasien melalui personalisasi layanan dan pemantauan berkelanjutan terhadap kebutuhan kesehatan individu. Namun demikian, implementasi customer relationship management masih menghadapi beberapa tantangan, antara lain keterbatasan infrastruktur teknologi, resistensi tenaga kerja, serta isu privasi dan keamanan data pasien. Sebagai kesimpulan, customer relationship management adalah instrumen strategis yang berkontribusi signifikan dalam meningkatkan mutu layanan kesehatan, sepanjang implementasinya didukung oleh kebijakan, regulasi, serta kesiapan sumber daya organisasi.Kata kunci: customer relationship management; mutu layanan kesehatan; kepuasan pasien; teknologi informasi